Prevalence and Associated Factors of Intradialytic Hypertension in a Resource-Constrained South Asian Hemodialysis Cohort: A Cross-Sectional Study - Qazi, Shayan Ali; Hashmat, Sana; Uzma Ibrahim; Kamran Khan (LIAQUAT MEDICAL RESEARCH JOURNAL, 2025)
A significant number of patients with end-stage renal disease (ESRD) experience a paradoxical rise in systolic blood pressure (SBP) during or immediately following hemodialysis (HD), a condition known as intradialytic hypertension (IDHTN). While the physiological removal of excess fluid typically lowers blood pressure, IDHTN has been linked to increased morbidity, hospitalization, and mortality. A cross-sectional study was conducted on 134 adults undergoing thrice-weekly maintenance HD at a tertiary care center in Karachi, Pakistan, to investigate the prevalence and associated factors of this condition in a resource-constrained setting where data are scarce. Intradialytic hypertension was defined as a change in SBP of at least 10 mmHg from pre- to post-dialysis, averaged over three consecutive sessions. The study found a prevalence of 35.8% (48 out of 134 patients). The condition was significantly associated with several factors, including pre-existing hypertension (p=0.005) and diabetes mellitus (p=0.012), ultrafiltration volumes below 2 L (p=0.020), and, most notably, the use of antihypertensive medications (p<0.001) and dialyzable agents (p<0.001). Additional associations were observed with age 30 years or younger (p=0.018) and smoking (p<0.001). The findings indicate that IDHTN is a common finding in this cohort and is strongly linked to clinical and treatment-related factors. The results suggest that interventions focused on optimizing ultrafiltration targets and tailoring antihypertensive regimens, particularly by selecting non-dialyzable agents, may be crucial for reducing the incidence of this condition and improving patient outcomes.